An environment that nurtures and supports relationships with children: nurturing and supporting storytelling - Dante, Klebshiela Raven (My University, 2023)
How does educator responsiveness nurture and support their relationships with children? This presentation emphasizes the role of educators as co-learners, co-researchers, and co-imaginers of possibilities alongside children. Being with children by listening, reflecting, observing, and extending their ideas deepens our understanding of them and their ideas. This is how we provide an environment that nurtures and supports children and their ideas. Using a cycle of inquiry, educators make meaning of what the children are doing that deepens their relationship with children and offer them an environment that nurtures and supports their ideas.
Keywords: educators; nurture; environment; children; Ideas that Matter